189k views
2 votes
How do you solve -9-6x+3=18

User Kamara
by
4.4k points

1 Answer

5 votes

Answer:

x = - 6

Step-by-step explanation:

Given the equation:


-9-6x+3=18

First, we arrange by bringing the numbers together as follows:


-6x-9+3=18

Next, simplify the left-hand side:


-6x-6=18

Then, we add 6 to both sides.


\begin{gathered} -6x-6+6=18+6 \\ -6x=24 \end{gathered}

Finally, we divide both sides by -6.


\begin{gathered} (-6x)/(-6)=(24)/(-6) \\ x=-4 \end{gathered}

The value of x is -4.

User ShashwatZing
by
4.9k points